Penyelesaian Sengketa Kepemilikan Tanah Adat Melalui Proses Pauhi dan Pahamang di Desa Rindi Praiyawang, Kabupaten Sumba Timur - Ngunjunau, Umbu Lapu; Nubatonis, Orpa J; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2025)
Land dispute resolution in indigenous communities is a complex process and is influenced by various social, cultural, and customary law factors. This study aims to analyze the Pauhi and Pahamang mechanisms as methods for resolving land disputes in indigenous communities and to identify the obstacles faced in their implementation. The research method used is a qualitative approach with in-depth interview techniques with customary leaders and communities involved in the dispute resolution process. The results of the study show that Pauhi functions as a deliberation mechanism that opens up space for dialogue for disputing parties, while Pahamang is a final decision-making stage. However, in its implementation, these two mechanisms face various challenges, such as lack of public awareness, minimal documentation, and the influence of personal interests in decision-making. In addition, external factors such as modernization and state law also influence the effectiveness of the customary system in resolving land conflicts. Therefore, efforts are needed to strengthen this customary mechanism by increasing coordination between customary stakeholders, recording decisions in writing, and integrating with the formal legal system to ensure the sustainability and effectiveness of land dispute resolution in indigenous communities.